Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.3 - Polynomial Functions, Graphs, and Composition - 4.3 Exercises: 28

Answer

6

Work Step by Step

We are given that $f(x)=x^{2}-9$, $g(x)=2x$, and $h(x)=x-3$. We are asked to find the value of $(f-g)(-3)$. We know that $(f-g)(x)=f(x)-g(x)$. Therefore, $(f-g)(-3)=((-3)^{2}-9)-(2(-3))=(9-9)-(2\times-3)=(0)-(-6)=0+6=6$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.